The Influence of Accounting Information Systems and Internal Control on the Quality Of Regional Financial Statements in the Government of Bondowoso District - Muhammad Deni Saputro (Journal of Contemporary Information Technology, Management, and Accounting, 2022)
This purpose of this research to determine the effect of accounting information systems and internal control systems on the quality of regional financial statements. In this study, the local government employees of Bondowoso Regency, the sample in this study were 50 respondents, financial and accounting staff at work units in Bondowoso. collected first using a questionnaire. The results of research conducted using SPSS prove that the independent variable accounting information system has a positive effect on local government financial reports and the internal control system has a positive effect on the quality of local government financial reports. So that local government financial reports will be able to meet the characteristics or value of information that improve the quality of local government financial reports, so that they get good opinions and have no exception a positive effect on the quality of regional financial reports. This study also has several limitations from several variables.